A methodology for implementing a water balance of ESKOM power stations using the online condition monitoring software EtaPRO - Sewlall, Preetha (Department of Mechanical Engineering, 2022)
Eskom produces approximately 90% of the electricity used in South Africa of which approximately 90.8% is from fossil fuel power plants. The process of electricity generation requires a significant quantity of raw water; therefore, Eskom is considered a strategic water user in South Africa. Water management is a growing focus area due to the increase in water usage and requires continuous improvement. Water management has been identified as an area lagging behind on the advanced analytics initiatives in Eskom. Excel based tools were used for the development of water balance models and water performance calculations in Eskom. This was attributed to the user-friendly functionality and availability to all users. However, the Excel tool posed challenges in allowing for standardisation and validation of calculations, tracking of model changes, continuous trending and storage of data as well as structured graphical user interfaces for screens and dashboard developments. There was therefore a need to develop a methodology on how to structure a water balance model for coal-fired power plants with standard calculation templates that allowed for customisation by each power plant within Eskom. It was required that the water balance model be implemented on a performance and monitoring tool allowing for comparison of power plant targets to actual online data in real time, enhancing the monitoring capabilities. It should have the ability to generate real time water performance data creating an opportunity for improved water management across the generation fleet. The approach adopted in this dissertation was to learn from existing Eskom Excel water balance tools and develop a standard mathematical model in the form of EtaPRO calculation templates. These templates are be structured such that they function as process components to develop water balances at power plants. The mathematical verification of the Excel calculations were to be conducted using Mathcad. The access to real time data, performance monitoring capabilities and availability at all Eskom Power plants, led to the selection of EtaPRO as the modelling platform. The research conducted led to the development of a methodology for setting up a water balance model for a wet-cooled coal-fired power plant. Calculation templates developed into EtaPRO were validated against the Mathcad mathematical model. The results included a well-documented mathematical model of a water balance in Mathcad and the development of 19 calculation templates that perform the function of standard process components. In addition to calculation templates, multiple Non Volatile (NV) records were created to allow the power plants to capture and track permanent data inputs. NV records also allow for creation of case studies, improving the process monitoring capabilities. A water balance model for a selected power plant was simulated in EtaPRO using the developed calculation templates and user defined formulae. Test screens and dashboards were created to illustrate how the calculation templates and water balance framework would be used to develop a typical water balance model and monitoring system. In conclusion, it is possible to develop process models within the EtaPRO software from well-defined mathematical models to address the performance monitoring concerns on water systems within Eskom.